Structural refinement and photoluminescence properties of cube-like (Ca1-xCux)TiO3 crystals synthesized by the microwave-hydrothermal method - Oliveira, Larissa H.; Moura, Ana P. de [UNESP]; Cavalcante, Laecio S. [UNESP]; Antonio, Selma G. [UNESP]; Longo, Elson [UNESP]; Varela, Jose A.; Laudon, M.; Romanowicz, B. (Crc Press-taylor & Francis Group, 2012)
In this work, (Ca1-xCux)TiO3 crystals with (x = 0, 0.01 and 0.02), labeled as CTO, CCTO1 and CCTO2, were synthesized by the microwave-hydrothermal method at 140 degrees C for 32 min. XRD patterns (Fig.1), Rietveld refinement and FT-Raman spectroscopy indicated that these crystals present orthorhombic structure Pbnm. Micro Raman and XANES spectra suggested that the substitution of Ca by Cu in A-site promoted a displacement of the [TiO6] [TiO6] clusters adjacent from its symmetric center, which leads distortions on the [CaO12] clusters neighboring and consequently cause the strains into the CaTiO3 lattice. FE-SEM images showed that these crystals have an irregular shape as cube like probably indicating an Ostwald-ripening and self-assemble as dominant mechanisms to crystals growth. The powders presented an intense PL blue-emission.
Keywords: Optical materials; Chemical synthesis; XANES; Luminescence; microcrystals